Pengaruh Pemberian Ekstrak Bunga Pepaya (Carica papaya L.) Terhadap Kadar Trigliserida Dan Indeks Lee Pada Tikus (Rattus norvegicus) Galur Sprague Dawley Jantan Yang Diberi Diet Tinggi Lemak - Dita Fitriani; Hetti Rusmini; Asmia Djunishap (Prodi Kedokteran Fakultas Kedokteran Universitas Malahayati, 2026)
Abstract: The Effect Of Papaya Flower Extract (Carica Papaya L.) On Triglyceride Levels And Lee Index In Male Sprague Dawley Rats (Rattus Norvegicus) Feeding A High-Fat Diet. The incidence of cardiovascular disease in Indonesia shows a high rate where the risk factor is hyperlipidemia. Hyperlipidemia is characterized by an increase in triglyceride levels. Lipids deposited in adipose tissue will cause an increase in the lee index. Papaya flowers that contain flavonoids, tannins and steroids play a role as anti-hyperlipidemia agent by inhibiting the activity of the enzyme HMG CoA reductase. This study aimed to determine the effect of papaya flower extract (Carica papaya L.) on triglyceride levels and lee index in male Sprague Dawley rats treated with high-fat diet. This research was conducted with pure experimental pre and posttest with group design control. The samples used were 25 male divided into 5 groups. The result of Paired T-test showed that there was significant increase in triglyceride and lee index level (p 0.05) after being given a high- fat diet in all treatment groups. After being given the papaya flower extract, there was a significant decrease in triglyceride levels in the P2 group (p = 0.031) and P3 (0.011) and a significant increase in the lee index in the P1 group. There is an effect of giving a high-fat diet to an increase in triglyceride levels and lee index. There is influence of papaya flower extract on triglyceride levels and lee index. But there is no significant dose difference.Keywords: High fat diet, Papaya flower extract, Lee Index, Triglycerides. Abstrak : Pengaruh Pemberian Ekstrak Bunga Pepaya (Carica Papaya L.) Terhadap Kadar Trigliserida Dan Indeks Lee Pada Tikus (Rattus Norvegicus) Galur Sprague Dawley Jantan Yang Diberi Diet Tinggi Lemak. Kejadian penyakit kardiovaskular di Indonesia menunjukan angka yang tinggi dimana faktor resikonya adalah hiperlipidemia. Hiperlipidemia ditandai salah satunya dengan meningkatnya kadar trigliserida. Lipid yang terdeposit pada jaringan adiposa akan menyebabkan peningkatan indeks lee. Bunga pepaya memiliki kandungan flavonoid dan tanin yang berperan dalam antihiperlipidemia dengan menghambat aktivitas enzim HMG KoA reduktase. Penelitian ini bertujuan untuk mengetahui pengaruh ekstrak bunga pepaya (Carica papaya L.) terhadap kadar trigliserida dan indeks lee pada tikus yang diberi diet tinggi lemak. Penelitian ini merupakan penelitian eksperimental murni dengan pre and post test with control group design. Sampel yang digunakan sebanyak 25 ekor tikus yang dibagi dalam 5 kelompok. Hasil uji Paired T-test menunjukan peningkatan kadar trigliserida dan indeks lee yang bermakna (p0.05) setelah diberi diet tinggi lemak pada semua kelompok perlakuan. Setelah diberi ekstrak bunga pepaya terjadi penurunan kadar trigliserida yang bermakna pada kelompok P2 (p=0.031) dan P3 (0.011) dan terjadi peningkatan indeks lee yang bermakna pada kelompok P1. Hasil penelitian menunjukkan terdapat pengaruh pemberian ekstrak bunga pepaya terhadap kadar trigliserida, namun tidak terdapat pengaruh pada indeks lee.Kata kunci :Diet tinggi lemak, Ekstrak Bunga Pepaya, Indeks Lee, Trigliserida.